Cases, simulations and experiential approaches - Galea, Chris (Teaching business sustainability ;, 2007)
If there is one area of business education that requires out-of-the-box, creative thinking it is sustainability. A companion to ""Teaching Business Sustainability 1: From Theory to Practice"", this collection of teaching pedagogies aims to create a learning environment where students themselves take control over their own learning.